Has the formation of disinfection by-products been overestimated? Membrane leakage from syringe filter heads serves as unexpected precursors. (November 2020) - Ou, Tian; Fang, Chao; Ding, Shunke; Zhao, Tiantao; Liu, Shaogang; Yu, Zhenxun; Chu, Wenhai
Abstract: Syringe filters are widely used for sample pretreatments in laboratories. This study found that, surprisingly, these filters can leak dissolved organic carbon (DOC) that can potentially serve as precursors of disinfection by-products (DBPs). Nine common types of syringe filters were assessed. The results showed that the DOC of ultrapure water increased after syringe filtration. The DOC shed from filter membranes was characterized, whose spectra showed that the main compounds exhibited a low apparent molecular weight. Five classes of DBPs were investigated including trihalomethanes, haloacetaldehydes, haloacetonitriles, haloacetamides and halonitromethanes, among which trichloromethane (TCM), dichloroacetaldehyde (DCAL), trichloroacetaldehyde (TCAL), dichloroacetonitrile (DCAN), and trichloronitromethane (TCNM) were principally detected. The DBP formation was affected by chlorination time and membrane types. In general, the use of the poly vinylidene fluoride membrane resulted in the highest formation of TCM and TCAL, whereas nylon and mixed cellulose esters membranes contributed significantly to the formation of DCAN and TCNM, respectively. The shedding DOC and the formation of TCM, DCAL and TCAL from filter membranes were mitigated effectively by pre-washing; however, the contribution of membrane leakage to DCAN and TCNM formation was still notable, even with a pre-wash volume of 50 mL. When unwashed syringe filters were used for a real water sample, the DBP formation increased by up to 73.2% compared to the pre-washed ones; particularly for TCNM it was always over 15%. Therefore, for better quality control in laboratories, more attention should be paid to the syringe filters during sample pre-treatments, particularly when DBP formation is being investigated. Graphical abstract: Image 1 Highlights: The DOC of water sample increased significantly after syringe filtrations. The shedding DOC exhibited mainly low apparent molecular weight (100–1000 Da). TCM and TCAL precursors markedly leaked from filter membranes. Pre-washing with 50 mL water substantially mitigated the leakage from filter membranes. Filter membranes made greater impacts on the formation of HALs, HANs and HNMs than THMs.